Effects of fat level and calorie-protein ratio on performance of finishing pigs - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1976)
One hundred twenty finishing pigs averaging 52.9 kg (116 lbs.) initially were used to study effects of fat level and calorie-protein (C:P) ratio on performance and carcass traits of pigs fed a sorghum-soybean meal basal ration. The basal ration contained 13.1% crude protein, 0.55% lysine, 0.68% calcium and 0.59% phosphorus. Fat (tallow) was added to the basal ration at the expense of sorghum at 0, 3, 6, and 9% while maintaining a constant C:P ratio. Also, 9% fat was added to the basal ration without adjusting the C:P ratio. With a constant C:P ratio, daily gain and feed efficiency were improved by adding fat. Pigs fed the basal ration supplemented with 9% added fat while maintaining a constant C:P ratio gained faster and were more efficient (P<.05) than pigs fed 9% added fat without adjusting the C:P ratio. Carcass data were collected on 75 pigs at approximately 100 kg (220 lbs.). Adding fat resulted in a small, yet significant (P<.05), increase in backfat thickness. However, carcass value, on a grade and yield basis, was not reduced by adding fat.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Fat; Calorie-protein ratio; Performance; Basal ration; Lysine